Educación formal y desarrollo de las destrezas de razonamiento y deliberación. Un estudio en alfabetización de adultos (1999)
The present article discuss the role of culture in shaping cognitive processes in hu¬man beings.Analyzing data fromTranscultural Psychology andAdult Literacy research we argue that theories which stress the role of maturation in the development of cognition fail in understanding the nature of human cognition. To support these ideas we conducted a research in an adult educational program to show that reason¬ing skills develop with educational experience.We analyze the reasoning skill through debates, a kind of practice that allows us to study reasoning in a everyday setting. Data shows that reasoning skills change in a very wide way as the educational expe¬rience of subject increase. Subjects more experienced in school tend to build argu¬ments in the debate using a more decontextualized discourse and implementing explanations as structure of their reasoning process. Low experienced subjects show higher preferences to contextulaized forms of discourse and using descriptions as core of their arguments.These data are discussed in light of the heterogenity theory of verbal thinking.